PENGARUH PELAKSANAAN PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGASI TERHADAP KEMAMPUAN BERPIKIR KRITIS (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2022)
This research is the quantitative research of types true with Pre-Test Post-Test Control Group Design. The research variables are: 1) The implementation of cooperative learning in the investigative group type (independent variable) and 2) Critical thinking ability (the dependent variable). The sampling of random. The results of the study showed that: 1) The implementation of learning cooperative type group investigation in learning social studies was carried out through six stage of learning and implemented  with well  because the process there was an increase in the learning process on sustainable in the first meeting  until fourth meeting :2)The critical thinking ability of the students experimental group with using the investigative group type cooperative has increased, 3) The critical thinking ability of students control group's with the implementation of conventional learning have not increased; 4) The implementation of learning cooperative type investigation group in social studies learning has an effect on students' critical thinking skills. Key words: Cooperative Type Group Investigation, Critical Thinking Ability